2008
DOI: 10.1024/1012-5302.21.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Validität der Waterlow-Skala zur Dekubitusrisikoeinschätzung auf der Intensivstation: eine prospektive Untersuchung an 698 Patienten

Abstract: Critically ill patients are at a particular risk for developing pressure ulcers. Yet until now, no sufficiently specific, validated pressure ulcer risk assessment instruments exist for critically ill patients. In a prospective study of 698 patients of medical intensive care unit (ICU), we therefore analyzed if the Waterlow scale is suitable for pressure ulcer risk assessment in the ICU. Only patients with no pressure ulcer on admission to the ICU were included. The Waterlow scale was used to assess pressure ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…Our data revealed a cut-off score of 19, which is approximately compatible with the results of Li et al (Chunpeng, 2019) and Chen et al (Chen, 2016), varying from 20 to 22 points for the perfect balance of SEN, SPN, PPV and NPV. We also found a higher cut-off score of 30 in a study of 689 patients in the ICU (Compton et al, 2008) and 25 points in the study by Weststrate et al (1998), confirming our results. The heterogeneity in different cutoffs may be associated with the average illness severity among critical patients, more severe patients in the ICU and a higher cut-off of the TA B L E 1 Reliability and Validity of the Waterlow scale in critically adult patients (N = 5874).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data revealed a cut-off score of 19, which is approximately compatible with the results of Li et al (Chunpeng, 2019) and Chen et al (Chen, 2016), varying from 20 to 22 points for the perfect balance of SEN, SPN, PPV and NPV. We also found a higher cut-off score of 30 in a study of 689 patients in the ICU (Compton et al, 2008) and 25 points in the study by Weststrate et al (1998), confirming our results. The heterogeneity in different cutoffs may be associated with the average illness severity among critical patients, more severe patients in the ICU and a higher cut-off of the TA B L E 1 Reliability and Validity of the Waterlow scale in critically adult patients (N = 5874).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our findings demonstrated that the Waterlow scale was overly predictive (Borghardt et al, 2015;Compton et al, 2008), with a high SEN of 62.7% and a low SPE of 57.4%. This result means that some patients receive more prophylactic treatment than they need (Wåhlin et al, 2021), which wastes medical resources.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, compared with Compton's study, our cut-off score was lower (30 vs. 23), because we included a higher proportion of male patients (61.6% vs. 56.2%) which may decreased the scores for 'sex' (Compton et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…For example, the average age of patients (60.68 ± 15.38 years) in our study was older than in the previous study (59.4 years) (Borghardt et al., 2015), which may increase the scores for ‘age’ item. In addition, compared with Compton's study, our cut‐off score was lower (30 vs. 23), because we included a higher proportion of male patients (61.6% vs. 56.2%) which may decreased the scores for ‘sex’ (Compton et al., 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Ein Dekubitus der Kategorie IV (EPUAP) bleibt dies auch nach der Abheilung des Defektes (Schröder 2009). (Compton et al 2008).…”
Section: Daniela Deufert Und Elfriede Fritzunclassified